Stocks or Options? Moral Hazard, Firm Viability, and the Design of Compensation Contracts - Kadan, Ohad; Swinkels, Jeroen M. (Review of Financial Studies, 2008)
We consider the choice between stocks and options to provide effort incentives to a risk-averse manager. We show that stocks can dominate options as a means of motivation only if nonviability risk is substantial, as in financially distressed firms or start-ups. Options dominate stocks for other firms. These results hold regardless of the existing portfolio of the manager. We provide empirical evidence that higher bankruptcy risk is indeed correlated with more use of stock. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.